A Conversion Layer Based on Trivalent Chromium and Cobalt for the Corrosion Protection of Electrogalvanized Steel - Di Sarli, Alejandro Ramón (2014)
The corrosion resistance of pure zinc coatings can be improved through the application of suitable chemical passivation treatments. Hexavalent chromium (Cr6+) compounds have widely been used to formulate conversion layers providing better anticorrosive protection as well as anchorage properties to painting systems. However, taking into account that they are produced using hazardous chemical compounds, the development of alternative and “green” technologies with equivalent protective performance is a paramount purpose of many R&D laboratories working around the world. In the present paper, the corrosion behavior of industrially electrogalvanized steel subjected to a Cr3+ + Co2+-based passivation treatment was studied. The experimental work involved electrochemical impedance spectroscopy (EIS)measurements and polarization curves in a 0.1 mol/L Na2SO4 solution, surface microstructural and morphological characterization by electronic microscopy as well as chemical analysis by EDXS and XPS. The most commonly observed failures on the Cr6+ treated sampleswere attributed to microstructural features of the substrate that were not adequately healed by the Cr6+ passivation treatment.